Proyek Pengaspalan Jalan dan Pembuatan Parit di Desa Balun Ijuk Gang Kost Sahpire – Jalan Jerambah Gantung - Amanda Amanda; Octavia Octavia; Aqif Abi Aufa; Ilham Maulana; M.Afdal S (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The road paving and ditch construction project in Balun Ijuk Village, particularly from Sahpire Boarding House Lane to Jerambah Gantung Road, aims to enhance transportation infrastructure to support mobility for local residents and students of Bangka Belitung University. This study employs a quantitative method with a financial feasibility analysis approach. Findings indicate that the total project cost is IDR 988,153,778 with an implementation duration of 2 months and 3 weeks. The financial analysis yields a Net Present Value (NPV) of IDR 481,705,602.62 (15%) and IDR 326,419,561.97 (20%), an Internal Rate of Return (IRR) of 18%, a Benefit Cost Ratio (BCR) of 1.48, and a Payback Period (PP) of 2 years and 7 months. Based on these results, the project is deemed economically viable with significant positive impacts on the community, including improved accessibility, reduced flooding risks via effective ditches, and enhanced connectivity and local economic activities. Additionally, the project implementation is expected to create temporary job opportunities and support sustainable infrastructure development in the region.